Tests of steel and composite CHS X-joints with curved chord under axial compression. (15th September 2015) - Chen, Yu; Feng, Ran; Wang, Chaoyang
Highlights: Steel and composite CHS X-joints with curved chord under axial compression were tested. Effects of curvature radius of chord member and concrete infill were evaluated. Ultimate strengths of steel and composite CHS X-joints are enhanced by hot-rolled bending. Current design rules are conservative for CHS X-joints with both straight and curved chords. Abstract: This paper presents an experimental investigation on empty and concrete-filled circular hollow section (CHS) X-joints with curved chord under axial compression. A total of 16 specimens was fabricated by hot-rolled bending the chord members into curvature with three different radii to apply axial compression force to the brace members, in which 6 specimens were tested with empty curved chord, 6 specimens were tested with concrete filled in the curved chord only, and 4 traditional empty and concrete-filled CHS X-joints with straight chord were also tested for comparison. The effects of curvature radius of chord member and concrete filled in the chord member on the joint strength and behavior were evaluated. It is shown from the comparison that the ultimate strengths of the CHS X-joints with curved chord are generally larger than those of the traditional CHS X-joints with straight chord. In addition, the ultimate strengths of the concrete-filled CHS X-joints are larger than those of the empty CHS X-joints, and the enhancement of the ultimate strengths of the traditional CHS X-joints with straight chord is much more pronounced than that of the CHS X-joints with curved chord.